Development and Validation of Stability Indicating RP-HPLC Method for the Simultaneous Estimation of Dapagliflozin Propanediol and Metformin Hydrochloride in Tablet Dosage Form (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
A rapid, precise, accurate, specific and simple stability indicating RP-HPLC method was developed for simultaneous estimation of Dapagliflozin Propanediol (DAPA) and Metformin Hydrochloride (MET) in its tablet dosage form. Method was performed on a column C8 Thermoquest, hypersil division of dimension 250 mm × 4.60 mm having particle size 5 micron. The mobile phase used in the method was 10 mM Ammonium Acetate buffer (pH- 4), Methanol and Acetonitrile in proportion of 30:65:05 respectively. The drug was subjected to acid and alkali hydrolysis, oxidation, photolysis and heat as stress conditions. The method was validated for specificity, linearity, range, precision, accuracy, robustness, LOD, LOQ and system suitability. The flow rate was maintained at 0.8 ml/ min and effluent was monitored at 227 nm. The retention time were observed 5.988 min and 4.661 min for DAPA and MET respectively. The standard curve was found linear over range of 60-140 μg/ml for DAPA and 300-700 μg/ml for MET with correlation coefficient of 0.9996 for DAPA and 0.9994 for MET. The limit of Detection (LOD) of this method was 1.121 μg/ml for DAPA and 6.162 μg/ml for MET. The limit of Quantitation (LOQ) of this method was 3.396 μg/ml for DAPA and 18.674 μg/ml for MET. The percentage recovery was found to be in the range of 98-102% at three different levels of a standard addition. The precision (repeatability, intra-day and inter-day) of the method was within the limit (RSD<2%). Degradation products produced because of stress studies did not interfere with the detection of DAPA and MET and the assay can thus be considered stability-indicating. Combination tablet was successfully analysed using the developed method.